Wastewater surveillance of enteric viruses in eastern Argentina: High rates of detection and first report of NoV GI.5 and GII.20 - Frydman, Camila Ayelen (2024)
Individuals infected with enteric viruses excrete them in their feces for an extended period, whether symptomatic or asymptomatic. This characteristic, combined with the capability of these viruses to persist in the environment, forms the core of our research. The objective of our study was to investigate the presence of viruses associated with diarrhea and hepatitis: Hepatitis A virus (HAV), Hepatitis E virus (HEV), Norovirus GI (NoV GI), Norovirus GII (NoV GII), and Rotavirus (RV) by RT-real time PCR, in untreated wastewater samples (n=100) collected in the period July 2020 to August 2021 from two low-income neighborhoods in the district of La Plata, Buenos Aires, Argentina. Globally, the percentage of positive samples was 25 % for HEV, 27 % for RV, 14 % for NoV GII, 1 % for NoV GI, and no detectable samples were found for HAV. HEV, RV, and NoV GII were detected in most of the studied months, with the highest detection rates of RV and NoV GII during the winter season. Regarding RV positive samples, the gene encoding the VP8* protein of three samples was sequenced and phylogenetic analysis revealed that the detected strains belonged to genotypes P[8] and P[3]. Additionally, four NoV strains were also genetically characterized by amplifying a fragment corresponding to the ORF-1/ORF-2 junction region. The identified strains were NoV GI.5, NoV GII.4, NoV GII.17 and NoV GII.20. Our results provide relevant information and serve as scientific evidence of the importance of considering wastewater analysis as a feasible strategy to determine the circulation of enteric viruses in the population, with the further benefit of predicting emerging strains. Moreover, this study represents the first report of the circulation of NoV GII.20 and GI.5 genotypes in our country.